The Role of Multicultural Education towards the Strengthening of Bhinneka Tunggal Ika (Case Study University of Muhammadiyah Metro) - Fatonah, Isti (LPPM IAIN Kudus, 2019)
The religious conflicts seem to correlate strongly with factors of non religion. Religion is usually a factor triggering the riots that preceded the conflict with economics, such as snatching parking lots, the area, and other factors. In other words, a small conflict often happens to be a huge deal. Multicultural education is education which notes the skill and knowledge base for the citizens of the world, it is important for students, penetrating all aspects of the education system, develop the attitudes, knowledge, and skills that enable students working for social justice. Process when a teacher and students together learn the importance of cultural variables for academic success as well as implement science education provides a critical attention to the social sciences and to help students to develop skills. Multicultural education is very important to minimize and prevent the occurrence of conflicts in some regions. Through education-based, multicultural attitudes and mindsets (the thinking) students will be more open to understand and appreciate diversity. In addition, the multicultural education are also useful for establishing ethnic diversity, race, religion, and culture (promoting diversity values). A key aspect in implementing multicultural education in schools is the absence of a policy that inhibits tolerance, including the absence of affront to race, ethnicity, and gender, cultivate sensitivity to against cultural differences.